2021
DOI: 10.12968/bjon.2021.30.9.562
|View full text |Cite
|
Sign up to set email alerts
|

Do not attempt resuscitation decisions during the COVID-19 pandemic

Abstract: Emeritus Professor Alan Glasper, from the University of Southampton, discusses concerns raised by the Care Quality Commission about the imposition of do not resuscitate orders on some patients during the pandemic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Echoing our initial survey study ( Ariyo et al , 2021 ), we found that undue influence was most often a concern in financial decisions, as well as for contact decisions after domestic abuse, and with older adults, people with learning disability and in brain injury. Circumstances of the COVID-19 pandemic have exacerbated some of the concerns: for example, with the increase in domestic violence ( Lindsey, 2020 ; Piquero et al , 2021 ) and questions around the validity of advance statements to refuse resuscitation in care homes ( Glasper, 2021 ; Griffith, 2020 ). Across the interviews, it was clear that the MCA 2005 was just one of several frameworks used in practice to safeguard adults when services suspect undue influence.…”
Section: Discussionmentioning
confidence: 99%
“…Echoing our initial survey study ( Ariyo et al , 2021 ), we found that undue influence was most often a concern in financial decisions, as well as for contact decisions after domestic abuse, and with older adults, people with learning disability and in brain injury. Circumstances of the COVID-19 pandemic have exacerbated some of the concerns: for example, with the increase in domestic violence ( Lindsey, 2020 ; Piquero et al , 2021 ) and questions around the validity of advance statements to refuse resuscitation in care homes ( Glasper, 2021 ; Griffith, 2020 ). Across the interviews, it was clear that the MCA 2005 was just one of several frameworks used in practice to safeguard adults when services suspect undue influence.…”
Section: Discussionmentioning
confidence: 99%